Feasibility and safety of transradial access for pediatric neurointerventions. (2nd April 2020) - Srinivasan, Visish M; Hadley, Caroline C; Prablek, Marc; LoPresti, Melissa; Chen, Stephanie H; Peterson, Eric C; Sweid, Ahmad; Jabbour, Pascal; Young, Christopher; Levitt, Michael; Osbun, Joshua W; Burkhardt, Jan-Karl; et al.
Abstract : Background: Diagnostic cerebral angiograms are increasingly being performed by transradial access (TRA) in adults, following data from the coronary literature supporting fewer access-site complications. Despite this ongoing trend in neuroangiography, there has been no discussion of its use in the pediatric population. Pediatric TRA has scarcely been described even for coronary or other applications. This is the first dedicated large study of transradial access for neuroangiography in pediatric patients. Methods: A multi-institutional series of consecutively performed pediatric transradial angiograms and interventions was collected. This included demographic, procedural, outcomes, and safety data. Data was prospectively recorded and retrospectively analyzed. Results: Thirty-seven diagnostic angiograms and 24 interventions were performed in 47 pediatric patients. Mean age, height, and weight was 14.1 years, 158.6 cm, and 57.1 kg, respectively. The radial artery measured 2.09+/-0.54 mm distally, and 2.09+/-0.44 mm proximally. Proximal and distal angiography were performed for both diagnostic and interventional application (17 distal angiograms, two distal interventions). Clinically significant vasospasm occurred in eight patients (13.1%). Re-access was successfully performed 11 times in seven patients. Conversion to femoral access occurred in five cases (8.2%). The only access-related complication was a small asymptomatic wrist hematoma after TR band removal. Conclusions: Transradial access in pediatric patients is safe and feasible. It can be performed successfully in many cases but carries some unique challenges compared with the adult population. Despite the challenge of higher rates of vasospasm and conversion to femoral access, it is worth exploring further, given the potential benefits.